2022
DOI: 10.1111/ijfs.15710
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of water in water Pickering emulsion containing gelatin and maltodextrin by bitter vetch protein nanoparticles

Abstract: The incompatibility between water soluble polymers is one of the interactions between the different constituents of the food systems, which eventually leads to system instability due to phase separation. The use of natural nanoparticles under the Pickering mechanism is a promising technique for the stabilisation of water-in-water (W/W) emulsions. In this study, bitter vetch protein nanoparticles (BPNs), which was produced by ultrasonic treatment, was used to stabilise W/W emulsion. Then additional tests were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…According to Lorén and Hermansson (2000), phase separation may occur because maltodextrin may be physically trapped in the gelatin matrix, and random coils may eventually link together to form triple helixes. So, these micrographs confirm the findings of the DLS and studies, in these types of emulsions, gelatin may act as both a continuous and dispersed phase, depending on the chemical characteristics and the relative volumes of the two biopolymers (Ansari & Shekarchizadeh, 2022;Beldengrün et al, 2018;Kasapis, Morris, Norton, & Clark, 1993a). Kasapis, Morris, Norton, and Clark (1993a) reported that the mixture of gelatin and maltodextrin may quickly become cloudy at high concentrations but appear absolutely transparent at low concentrations.…”
Section: Microscopic Imagessupporting
confidence: 85%
See 1 more Smart Citation
“…According to Lorén and Hermansson (2000), phase separation may occur because maltodextrin may be physically trapped in the gelatin matrix, and random coils may eventually link together to form triple helixes. So, these micrographs confirm the findings of the DLS and studies, in these types of emulsions, gelatin may act as both a continuous and dispersed phase, depending on the chemical characteristics and the relative volumes of the two biopolymers (Ansari & Shekarchizadeh, 2022;Beldengrün et al, 2018;Kasapis, Morris, Norton, & Clark, 1993a). Kasapis, Morris, Norton, and Clark (1993a) reported that the mixture of gelatin and maltodextrin may quickly become cloudy at high concentrations but appear absolutely transparent at low concentrations.…”
Section: Microscopic Imagessupporting
confidence: 85%
“…So, these micrographs confirm the findings of the DLS and Zeta potential experiments, which indicate that the system may become unstable following melting at 37°C. According to previous studies, in these types of emulsions, gelatin may act as both a continuous and dispersed phase, depending on the chemical characteristics and the relative volumes of the two biopolymers (Ansari & Shekarchizadeh, 2022; Beldengrün et al, 2018; Kasapis, Morris, Norton, & Clark, 1993a). Kasapis, Morris, Norton, and Clark (1993a) reported that the mixture of gelatin and maltodextrin may quickly become cloudy at high concentrations but appear absolutely transparent at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The particles can be very varied, and recent examples include cellulose microfibrils or nanocrystals in maltodextrin-in-dextran emulsions [19,20], β-lactoglobulin in dextran and hydroxypropyl methylcellulose aqueous mixtures [21], and platelet-like starch nanocrystals in PEG-in-dextran (P/D) emulsions [22], among other examples [23][24][25]. Stabilization of W/W requires an accurate control of particle adsorption at the interface (Figure 1).…”
Section: Stabilization By Adsorption Of Particles At Water/water Inte...mentioning
confidence: 99%
“…Te stabilization of w/w emulsions is an area that has recently attracted the interest of researchers and can trigger technological innovations, especially in the food industry [21][22][23][24][25], pharmaceutical [26], and biomedicine [27]. Te formulation of functional foods with a low fat content from w/w emulsions can mean new applications in the food industry [28].…”
Section: Introductionmentioning
confidence: 99%